2011
DOI: 10.1186/1476-069x-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and anemia as risk factors for pneumonia in ecuadorian children: a retrospective cohort analysis

Abstract: BackgroundAmbient air pollution and malnutrition, particularly anemia, are risk factors for pneumonia, a leading cause of death in children under five. We simultaneously assessed these risk factors in Quito, Ecuador.MethodsIn 2005, we studied two socioeconomically similar neighborhoods in Quito: Lucha de los Pobres (LP) and Jaime Roldos (JR). LP had relatively high levels of air pollution (annual median PM2.5 = 20.4 μg/m3; NO2 = 29.5 μg/m3) compared to JR (annual median PM2.5 = 15.3 μg/m3; NO2 = 16.6 μg/m3). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 22 publications
2
34
1
1
Order By: Relevance
“…24 Low hemoglobin level was found to be an independent risk factor for ALRTIs as it was detected in 56.25% of bronchiolitis cases, 62.5% of pneumonia cases and 42.71% of the control group (P = 0.044). 23 These data came in concordance with the study done by Harris et al 25 These authors studied anemia and air pollution as risk factors for ARLTIs and found that anemic children were at increased risk of hospitalization after an acute respiratory infection when compared to healthy nonanemic children. They explained their findings by hypothesis that anemia independently decreases oxygen delivery to tissue thereby enhancing poor tissue oxygenation which remains a central pathophysiological deficit in ARTIs.…”
Section: Discussionsupporting
confidence: 80%
“…24 Low hemoglobin level was found to be an independent risk factor for ALRTIs as it was detected in 56.25% of bronchiolitis cases, 62.5% of pneumonia cases and 42.71% of the control group (P = 0.044). 23 These data came in concordance with the study done by Harris et al 25 These authors studied anemia and air pollution as risk factors for ARLTIs and found that anemic children were at increased risk of hospitalization after an acute respiratory infection when compared to healthy nonanemic children. They explained their findings by hypothesis that anemia independently decreases oxygen delivery to tissue thereby enhancing poor tissue oxygenation which remains a central pathophysiological deficit in ARTIs.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings underscore the fact that even poor nutrition or marginal malnutrition can predispose children to pneumonia. Anemia also significantly increases the risk of pneumonia in children (Harris et al 2011). Anemia also significantly increases the risk of pneumonia in children which indicate that anemia might be a risk factor for lower respiratory tract infections including pneumonia; however further studies are needed to confirm this association.…”
Section: Figure-1: Percent Distribution Of Children By Different Catementioning
confidence: 85%
“…Childhood pneumonia is the world's leading causes of death among children [1][2][3], with about 800000 deaths annually of children <5 years of age [4,5]. Pneumonia is also the leading cause of death in children <5 years old in China [6] and one of the leading causes of death in adults in China [7].…”
mentioning
confidence: 99%